Integrasi proses elektrokoagulasi-elektrooksidasi sebagai alternatif dalam pengolahan limbah cair batik zat warna naftol - Fikry Nashrullah K; Muslikhin Hidayat; Moh. Fahrurrozi (Jurnal Rekayasa Proses, 2016)
The production of batik produces wastewater which contains mixture of complex organic macromolecules. In this study, a sequential process of electrocoagulation-electrooxidation (EC-EO) using electrodes of aluminium-graphite and PbO2-graphite was proposed as an alternative method for treating wastewater of naphthol from batik dyeing process. The effects of parameter of current density of in the range of 3.7-7.90 mA/cm2, and the effect of electrical voltage to the decrease of color intensity. The electrocoagulation-electrooxidation method was carried out in a batch reactor with a capacity of 1.3 L, where the first 20 minutes is the electrocoagulation process and the next 100 minutes is the electrooxidation process. The samples were drawn at 10, 20, 40, 60, 80, 100 and 120 minutes and their color intensity was analyzed using spectrophotometric method. The results showed that the highest decreased value was at 99,78% at the current density (7,53 mA/cm2) during 120 minutes with electricity consumption 14,40 kWh/m3. The higher the density of the current, the greater the decrease value of color intensity in the liquid naphthol waste.